Comparative analysis of morphology, resource allocation, and nutritional characteristics in populations of Festuca dolichophylla cultivated in the Andean region of Peru - Paucar, Ysai (2026)
Grasslands are ecosystems of global importance; in Peru, they represent more than half of the country's territory. However, few studies have been conducted on high Andean grasslands. The objective was to study morphological, productive, resource allocation, and nutritional characteristics in five populations of Festuca dolichophylla grown under similar conditions. Populations that originated from Huancavelica Community and University, Junín, Pasco, and Puno were grown in Huancavelica Community in a randomized block design. After twelve months, a uniformization cut was performed, and five months later they were evaluated. Morphological characteristics, productivity, and resource allocation were analyzed with ANCOVA, the nutritional characteristics were analyzed with one-way ANOVA (considering population as a factor). Significant differences (p < 0.05) were found for morphological characteristics such as height, number and length of stems, and number of inflorescences. The resource allocation was 13.8% root, 18.4% crown, 29.2% culms + sheaths, 34.8% blades, and 3.8% inflorescence, with no differences between populations (p > 0.05). The Puno population stood out for its greater biomass, linked to more stems and inflorescences. Nutritional characteristics varied among populations in terms of crude fiber, neutral detergent fiber, acid detergent fiber, and in vitro dry matter digestibility. These findings are useful for selecting populations in revegetation or genetic breeding programs.